Understanding Caregiver Quality of Life in Caregivers of Hospitalized Older Adults With Cancer. Issue 5 (22nd March 2019) - Hsu, Tina; Nathwani, Nitya; Loscalzo, Matthew; Chung, Vincent; Chao, Joseph; Karanes, Chatchada; Koczywas, Marianna; Forman, Stephen; Lim, Dean; Siddiqi, Tanya; Stein, Anthony; Twardowski, Przemyslaw; et al.
Abstract : BACKGROUND/OBJECTIVES: Caregivers of older adults with cancer assist both with cancer care and other health issues, which may make them vulnerable to consequences of caregiving. Hospitalization may represent a time when a caregiver's ability to provide care at home is exceeded. We sought to characterize caregivers of hospitalized older adults with cancer, determine their quality of life (QOL), and identify factors associated with caregiver QOL. METHODS: Patients (n = 100), aged 65 years and older, with an unplanned hospitalization and their caregivers were included. Caregivers completed a questionnaire about their health, social support, caregiving relationship, QOL (Caregiver Quality of Life Index‐Cancer [CQOLC] tool), and patient function. Patient medical history was obtained via chart review. The association between patient, caregiving, and caregiver factors and CQOLC was determined using multivariate linear regression. RESULTS: Most patients (73%) had metastatic/advanced disease, and 71% received treatment for their cancer within 30 days of hospitalization. Median Karnofsky Performance Status (KPS) was 60%, and 89% required help with instrumental activities of daily living, as reported by caregivers. Median caregiver age was 65 years (range = 29‐84 years). The majority (60%) had no major comorbidities and rated their health as excellent/good (79%), though 22% reported worsening health due to caregiving. Caregivers had a median Mental Health Inventory‐18 score of 70 (range = 0–97), a median Medical Outcomes Study (MOS)‐social activity score of 56 (range = 0–87.5), and a median MOS‐Social Support Survey score of 68 (range = 0–100). Caregivers provided a median of 35 hours of care per week (range = 0‐168 hours of care per week). Mean CQOLC was 84.6 ± 23.5. Lower caregiver QOL was associated with poorer caregiver mental health, less social support, and poorer patient KPS ( P < .05). CONCLUSION: Caregivers of hospitalized older adults with cancer are older but generally in good health. Those with poorer mental health, less social support, and caring for patients with poorer performance status are more likely to experience lower QOL. J Am Geriatr Soc 67:978–986, 2019.